Pemanfaatan Literacy Information and Communication of Technology Google Sites bagi Peserta Didik - Ade Fricticarani; Dandi Rizky Oktariansyah; Redian Putra; Sirozul Qory; Tatu Humrotul (STKIP Andi Matappa Pangkep, 2024)
The era of revolution 5.0 is an era of development and improvement from revolution 4.0. In this era, technological developments continue to increase so that the use of ICT as a medium or tool, manipulation, and management of information is growing rapidly so that Information and Communication of Technology Literacy is needed, especially for the world of education. Information and Communication of Technology literacy is a person's ability to use technology and information applications effectively and efficiently. In the current era of learning, ICT is needed, one of which is a google site. Google site is one of the free website services used for learning media. The ease of obtaining learning media is becoming increasingly widespread, so that the information obtained by students is not only sourced from textbooks, but can also be obtained from outside when they can use digital devices properly. Various learning activities and needs such as collecting, preparing, storing, processing, reviewing, and disseminating information can use digital information technology. This technology can be a tool to facilitate various information needs in the learning process that can increase knowledge and understanding for students well.